Immature platelets in patients with acute coronary syndromes - Grove, Erik Lerkevang; Hvas, Anne-Mette; Kristensen, Steen Dalby (Thrombosis and Haemostasis, 2009)
Platelets newly released from the bone marrow are RNA-containing and more haemostatically active than mature platelets. Immature platelets are reliably quantified by flow cytometry, and the immature platelet fraction (IPF) reflects platelet production and the rate of platelet turnover. It was the objective of this study to evaluate the presence of immature platelets in healthy subjects, patients with stable coronary artery disease (CAD) and patients with acute coronary syndromes. Flow cytometric determination of immature platelets was performed with an automated analyzer (Sysmex XE-2100) using RNA fluorescent dyes. IPF was determined in 420 individuals: 22 healthy subjects, 39 patients with stable CAD, 182 patients with unstable angina/ non-ST-segment elevation myocardial infarction (non-STEMI) and 177 patients with acute STEMI. The geometric mean [95% confidence interval] of IPF was 2.51 [2.04–3.10] in healthy subjects, 2.87 [2.45–3.36] in CAD patients, 2.93 [2.72–3.15] in the non-STEMI/unstable angina group and 3.71 [3.45–3.99] in patients with STEMI (ANOVA: p < 0.0001). This difference remained significant after adjusting for baseline characteristics (p = 0.0003). In active smokers, IPF was 18% higher than in non-smoking individuals (p = 0.007), and IPF was 16% higher in diabetics compared with non-diabetics (p = 0.060). In conclusion, the fraction of immature platelets is increased in acute coronary syndromes, especially in the acute phase of STEMI. Immature platelets with an increased haemostatic potential may contribute to coronary thrombus formation.
Keywords: Atherothrombosis; arterial thrombosis; aspirin resistance; myocardial infarction; thrombopoiesis